Implementasi Pendekatan “Connected Learning” untuk Edukasi Secara Kreatif dan Sosial pada Interior Perpustakaan di Surabaya - Maureen Kresentia; Mariana Wibowo (Intra, 2019)
Surabaya City Public Library in Rungkut as a learning facility for the community needs to be supported by innovative interior space approach “Connected Learning” which is applied to 11-24 years old people to create creative and social educative learning based on visitor’s personal interests. This approach is used because its align with today focus about improving skills and literacy in using information. “Connecting People” concept was chosen to make the library design connects visitor, staff, and community with rooms that support “Connected Learning”, so the library is no longer just a place to read, but can be a place to develop interests creatively and socialy with the support of photography room, music room, computer and audio visual room, gallery, community space, maker space, and training space. This concept focused on 3 things, flexible, collaborative, and open space that is applied in open space library layout that connect the reading space and its supporting spaces. Thus, Surabaya City Public Library can be a flexible, collaborative, and supportive place for creative and social education based on young people’s personal interests.